1999
DOI: 10.1007/s004210050490
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exhausting stretch-shortening cycle exercise on the time course of mechanical behaviour in the drop jump: possible role of muscle damage

Abstract: The purpose of the present study was to investigate the effect of stretch-shortening-cycle-induced muscle damage on the time course of mechanical behaviour in the drop jump. Ten healthy male subjects performed submaximal stretch-shortening cycle (SSC) exercise on a special sledge apparatus. Exhaustion occurred on average within 3 min. A drop jump (DJ) test from a 50-cm height was performed before and immediately after the sledge exercise as well as 2 h, 2 days and 4 days later. The fatigue exercise showed rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
73
1
3

Year Published

2000
2000
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(82 citation statements)
references
References 31 publications
5
73
1
3
Order By: Relevance
“…Aspects of the bimodal trend for recovery after a fatigue workout, as indicated by Horita et al (27) and Komi (29), are evident in this study. The initial dramatic decline in DJ and RBJ performances was followed by a gradual improvement in performance at the subsequent recovery intervals up to the point where some variables were enhanced at the 300-second interval.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…Aspects of the bimodal trend for recovery after a fatigue workout, as indicated by Horita et al (27) and Komi (29), are evident in this study. The initial dramatic decline in DJ and RBJ performances was followed by a gradual improvement in performance at the subsequent recovery intervals up to the point where some variables were enhanced at the 300-second interval.…”
Section: Discussionsupporting
confidence: 74%
“…Horita et al (27) reported an early recovery 2 hours postfatigue, but no potentiation effect was reported for the DJ. Horita et al (25) again examined the effect of a repeated exhaustive submaximal SSC fatigue protocol on DJs that were performed 20 minutes and 2 and 4 days after the workout.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…For participants who decreased stiffness following exercise this would suggest more of a yielding action during the ground contact phase. Horita et al (1999) demonstrated that short duration exhaustive SSC exercise (3 min) reduced stiffness, increased joint extension at touchdown, thus enabling a greater yielding action. The authors speculated that the observed changes in stiffness were the result of altered prelanding motor commands, which is substantiated by the relationship between changes in feedforward activity and stiffness observed in the present study.…”
Section: Discussionmentioning
confidence: 97%